Pig‐to‐baboon heterotopic heart transplantation – exploratory preliminary experience with pigs transgenic for human thrombomodulin and comparison of three costimulation blockade‐based regimens. (3rd April 2015) - Iwase, Hayato; Ekser, Burcin; Satyananda, Vikas; Bhama, Jay; Hara, Hidetaka; Ezzelarab, Mohamed; Klein, Edwin; Wagner, Robert; Long, Cassandra; Thacker, Jnanesh; Li, Jiang; Zhou, Hao; et al.
Abstract Background Three costimulation blockade‐based regimens have been explored after transplantation of hearts from pigs of varying genetic backgrounds to determine whether CTLA4‐Ig (abatacept) or anti‐CD40mAb+CTLA4‐Ig (belatacept) can successfully replace anti‐CD154mAb. Methods All pigs were on an α1, 3‐galactosyltransferase gene‐knockout/CD46 transgenic (GTKO.CD46) background. Hearts transplanted into Group A baboons (n = 4) expressed additional CD55, and those into Group B (n = 3) expressed human thrombomodulin (TBM). Immunosuppression included anti‐thymocyte globulin with anti‐CD154mAb (Regimen 1: n = 2) or abatacept (Regimen 2: n = 2) or anti‐CD40mAb+belatacept (Regimen 3: n = 2). Regimens 1 and 2 included induction anti‐CD20mAb and continuous heparin. One further baboon in Group B (B16311) received a modified Regimen 1. Baboons were followed by clinical/laboratory monitoring of immune/coagulation parameters. At biopsy, graft failure, or euthanasia, the graft was examined by microscopy. Results Group A baboons survived 15 to 33 days, whereas Group B survived 52, 99, and 130 days, respectively. Thrombocytopenia and reduction in fibrinogen occurred within 21 days in Group A, suggesting thrombotic microangiopathy (TM), confirmed by histopathology. In Group B, with follow‐up for >4 m, areas of myofiber degeneration and scarring were seen in two hearts at necropsy. A T‐cell response was documented only in baboons receiving Regimen 2. Conclusions The combination of anti‐CD40mAb+belatacept proved effective in preventing a T‐cell response. The expression of TBM prevented thrombocytopenia and may possibly delay the development of TM and/or consumptive coagulopathy.